Cu(I)–Bis(phosphine) Dioxides as Catalysts for the Enantioselective α-Arylation of Carbonyl Compounds - Escudero-Casao, Margarita; Licini, Giulia; Orlandi, Manuel (Synlett, 2021)
The transition-metal-catalyzed α-arylation of carbonyl compounds was first reported by Buchwald and Hartwig in 1997. This transformation has been used and studied extensively over the last two decades. Enantioselective variants were also developed that allow for controlling the product stereochemistry. However, these suffer several limitations in the context of formation of tertiary stereocenters. Presented here is our group’s contribution to this research area. The chiral Cu-bis(phosphine) dioxides catalytic system that we reported allowed accessing the enantioselective α-arylation of ketones that were not suitable for this transformation before in good yields and er up to 97.5:2.5. Preliminary insight and speculation concerning the reaction mechanism involving the unusual pairing of bis(phosphine) dioxides with transition-metal catalysts is also given.1 Introduction2 State of the Art3 Enantioselective α-Arylation of Acyclic Ketones4 Summary and Conclusions
Keywords: Cu catalysis; asymmetric catalysis; ligand design; α-arylation; bis(phosphine) dioxides